2021
DOI: 10.1371/journal.pone.0258970
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and viral load dynamics of COVID-19 in a mildly or moderately symptomatic outpatient sample

Abstract: Background Studies of outpatients with mild or moderate COVID-19 are uncommon. We studied: 1) association of symptoms with reverse transcriptase polymerase chain reaction (RT-PCR) test results; and 2) association of initial RT-PCR cycle threshold (Ct) in relation to duration of RT-PCR positivity in outpatients with mild or moderate COVID-19. Methods This was a cohort study of outpatients with confirmed COVID-19 and at least one symptom. Participants had repeat nasopharyngeal swabs and symptom checklists ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…S3 ). Furthermore, it is important to remark that the range of virus concentrations employed in this study correspond to most common viral loads found in COVID-19 patients at early stages of the infection ( Caplan et al, 2021 ; Soria et al, 2021 ), being therefore appropriate for the evaluation of antiviral therapies for early treatment.…”
Section: Resultsmentioning
confidence: 89%
“…S3 ). Furthermore, it is important to remark that the range of virus concentrations employed in this study correspond to most common viral loads found in COVID-19 patients at early stages of the infection ( Caplan et al, 2021 ; Soria et al, 2021 ), being therefore appropriate for the evaluation of antiviral therapies for early treatment.…”
Section: Resultsmentioning
confidence: 89%
“…With respect to the length time of the problem with clinical introductions, the current uncovered that there was a noteworthy affiliation (P<0.05) with the out come . In past study, it was concluded that in decently debilitated COVID-19 outpatients, genuine time -PCR tests held on positive along 49 days (47). Additionally, the test inspiration and term of the indication term related essentially with the introductory viral stack (47).…”
Section: Discussionmentioning
confidence: 99%
“…In past study, it was concluded that in decently debilitated COVID-19 outpatients, genuine time -PCR tests held on positive along 49 days (47). Additionally, the test inspiration and term of the indication term related essentially with the introductory viral stack (47). The height of viral stack is exceptionally conceivably to be the vital figure forcing overburden to body's resistant reaction that would be go with movement into extreme sickness (48).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, transmission often takes place before adequate control measures have been taken. Although a multitude of studies have compared the prevalence of symptoms between COVID-19 negative and COVID-19 positive LTCF residents, most had a limited number of residents or observed symptoms [1,[24][25][26][27][28][29]. Additionally, few studies have examined the relationship between viral load and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Viral load can be used as an indication for the degree of infectiousness and the prognosis of COVID-19 [26,[30][31][32]. LTCFs would benefit from a better understanding of which symptoms are related to different levels of viral load, as well as how viral load differs between LTCF staff and residents, for men and women.…”
Section: Introductionmentioning
confidence: 99%